A Summary of N and K Research with Strawberry in Florida - George Hochmuth; Ed Hanlon (EDIS)
More than 50 years’ worth of strawberry fertilization research has been conducted in Florida. This revised 25-page fact sheet reviews literature from all sources that pertain to commercial strawberry fertilization in Florida’s growing conditions. Written by George Hochmuth and Ed Hanlon and published by the UF Department of Soil and Water Science, March 2011.